Students’ perception in the use of shadowing techniques on listening skills in English Education study program University of Lampung - Sholihah, Lilis; Supriady, Deddy; Shalma, Diana; Agrifinna, Dinda (U-Jet Unila Journal of English Language Teaching, 2025)
One of the receptive skills is listening, which involves understanding the speaker's uttered words. The frequency with which learners practice hearing English language expressions has an impact on their listening abilities. One benefit is the abundance of resources available for use in teaching listening, such as easily accessible podcasts and YouTube videos. But teaching strategies and tactics are just as vital as the media, which is one of the key elements for listening skills. It is well recognized that S1 Language Education students’ listening skills still require development. The researcher administered listening practice which is called shadowing technique in which the students have to practice listening from the podcast, Youtube video and conversations. Then, they are assigned to repeat after the speakers’ utterance. The researchers conducted a pre-test of listening abilities before the listening class in order to conduct a pre-survey, but the outcomes were still far from the perfections. Their listening’s’ skill need to be improved. It is believed that by employing the Shadowing Technique, students' proficiency will grow. Thus, the goal of this study is to know the students’ perceptions on the use of shadowing technique in listening class of English Education students of FKIP University of Lampung. The research uses quantitative method with questionnaire as the instrument of the study. The sample of this study is S1 students of the English Education Study Program, FKIP University of Lampung, consisting of 27 of 2th semester students who take pre-intermediate listening course. The shadowing technique using YouTube videos and podcasts is expected to improve students' listening skills. The results have produced some interesting finding.